Supplier Evaluation and Selection by Using the Analytic Hierarchy Process (AHP): A case study - Pham , Cao Văn; Nguyen , Trung Tín (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Supplier selection is a critical activity in the supply chain, directly affecting a company’s business performance. One of the effective methods for evaluating and selecting suppliers in multi-criteria decision-making problems is the Analytic Hierarchy Process (AHP). This study employs a quantitative approach to assess and select suppliers for a company in Vietnam. The findings demonstrate that AHP is an effective tool for supplier selection. Furthermore, the study suggests future research directions by integrating AHP with other methods to enhance decision-making accuracy.